1992
DOI: 10.1128/aac.36.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Lipid complexing decreases amphotericin B inflammatory activation of human neutrophils compared with that of a desoxycholate-suspended preparation of amphotericin B (Fungizone)

Abstract: Amphotericin B (AmB) has toxic effects and alters neutrophil (polymorphonuclear leukocyte [PMN]) function. A lipid-complexed formulation of AmB (AmB-LC) has been reported (A. S. Janoff, L. T. Boni, M. C. Popescu, S. R. Minchey, P. R. Cuilis, T. D. Madden, T. Taraschi, S. M. Gruner, E. Shyamsunder, M. W. Tate, R. Mendelsohn, and D. Bonner, Proc. Natl. Acad. Sci. USA 85:6122-6126, 1988) to be less toxic than a desoxycholate-suspended preparation of AmB (AmB-des; Fungizone). In this study we compared the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
3
9
0
Order By: Relevance
“…We have reported that concentrations of AmB corresponding to peak levels in serum have little effect on PMN viability in vitro (55). We have also noted that AmB has little effect on PMN or MNL chemiluminescence by itself, but that it primes PMN for increased chemiluminescence in response to fMLP.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…We have reported that concentrations of AmB corresponding to peak levels in serum have little effect on PMN viability in vitro (55). We have also noted that AmB has little effect on PMN or MNL chemiluminescence by itself, but that it primes PMN for increased chemiluminescence in response to fMLP.…”
Section: Resultsmentioning
confidence: 86%
“…AmB also activates macrophages (15,34,48,66,67) and induces the production of tumor necrosis factor alpha (TNF-ot) and interleukin-1 beta (IL-1,8) (17,25). We have observed that the presence of mononuclear leukocytes (MNLs) exacerbates the inflammatory effects of AmB on PMN function, including AmB priming of the PMN oxidative burst and PMN expression of the adherence integrin Mac-1 (55).…”
mentioning
confidence: 99%
“…While the reported effects of amphotericin B formulations on O 2 Ϫ production by human phagocytes have been contradictory (18,22,25,26), in the present study none of the amphotericin B formulations affected O 2 Ϫ production from pretreated MNCs in response to either nonopsonized or serum-opsonized A. fumigatus hyphae. The exception was the ABLC-treated MNCs, which at the high concentration of ABLC, 25 g/ml, significantly reduced the production of O 2 Ϫ in response to serum-opsonized A. fumigatus hyphae.…”
Section: Discussionmentioning
confidence: 39%
“…Specifically, DAMB and ABLC were found to additively augment the fungicidal activity of pulmonary alveolar macrophages against conidia of A. fumigatus (17). However, the studies of the effects of DAMB on oxidative burst of phagocytes as evidenced by O 2 Ϫ production have shown contradictory results (18,22,25,26). To date, there are no reports published on the comparative effects of the four formulations on the antifungal activity of monocytes (MNCs) against A. fumigatus.…”
mentioning
confidence: 97%
“…Furthermore, it enhances the killing abilities of PMNs or macrophages (2, 5, 15, 19, 31, 33, 37-39, 41, 42, 47, 52, 59, 61, 65). The ability of amphotericin B to increase the activities of PMNs and macrophages may be the reason for its inflammatory properties (52,53). The allylamines (naftifine and terbinafine), a new generation of broad-spectrum antimycotic compounds, have recently been developed; they act by interfering with squalene 2,3-epoxidase, which results in decreased amounts of the principal membrane sterols, especially ergosterol (44,48).…”
mentioning
confidence: 99%